2011
DOI: 10.2105/ajph.2010.191759
|View full text |Cite
|
Sign up to set email alerts
|

Drug Arrests and Injection Drug Deterrence

Abstract: Deterrence-based approaches to reducing drug use seem not to reduce IDU prevalence. Alternative approaches such as harm reduction, which prevents HIV transmission and increases referrals to treatment, may be a better foundation for policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Providing public health and harm reduction advocates with young IDUs estimates can: (1) assist efforts to plan young IDU-related health services; (2) bring about a better understanding of young IDU drug-related health problems; and (3) assist research in exploring the social and structural determinants of young IDU-related prevalence [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…Providing public health and harm reduction advocates with young IDUs estimates can: (1) assist efforts to plan young IDU-related health services; (2) bring about a better understanding of young IDU drug-related health problems; and (3) assist research in exploring the social and structural determinants of young IDU-related prevalence [19, 20]. …”
Section: Introductionmentioning
confidence: 99%
“…Lifetime arrests and lifetime incarceration were distinct measures (Friedman et al, 2011). We used duration of incarceration, not timing of incarceration (how long ago incarceration occurred), as duration of incarceration was more important to predicting risk-taking sexual behavior (Khan et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous research on HIV and AIDS among PWID in these MSAs (23, 24, 26, 27, 31, 34) has indicated that a number of social and economic variables (see Table 1) should be controlled for. Some of these were available only for Census years 1990 and 2000.…”
Section: Methodsmentioning
confidence: 99%
“…See Friedman et al (2006, 2011 2013) for data on their relationship to key parameters for people who inject drugs (26, 27, 34). …”
Section: Tablementioning
confidence: 99%